Is burnout a turnout in university-based student organizations? Understanding the drivers of student leaders’ turnover - Balbon, Cleantha Sidney (Animo Repository, 2021)
This research compared four different conceptual models and determined which best predicts turnover intention and behavior among student officers in professional student organizations. These four models are: (1) Integration of Career Construction and Social Exchange Theories (Zhu et al., 2019); (2) Social Exchange Theory (Mulki et al., 2013); (3) Job Demands-Resources Theory (Bakker & Demerouti, 2004); and (4) Theory of Planned Behavior (Ajzen, 1985). The research was divided into two parts. Study 1 covers turnover behavior among student officers in De La Salle University. Study 2 is further divided into Part 1, where turnover intention among De La Salle University students was tested; and Part 2, where the same was tested for three universities: University of the Philippines, Ateneo de Manila University, and University of Santo Tomas. Additionally, the researchers included Coronavirus disease as a moderating variable for both studies. All parts of the research used the Partial Least Squares-Structural Equation Modeling statistical tool. Findings revealed that the Job Demands-Resources Theory by Bakker and Demerouti (2004) was most consistent in determining turnover intention and behavior among student officers in professional student organizations. All factors considered, the proposed model inWUodXced FacXlW\ AdYiVeU¶V EngagemenW and QXaliW\ of Relationship with Co-officers as moderating variables between Work-Related Burnout and Turnover Intention; and between Subjective Norms and Turnover Intention. By determining the model that best predicts turnover intention among student officers, student organizations are better equipped to reduce the number of student officers leaving their respective organizations, which is key to preserving the organization's standards.